2020
DOI: 10.3390/ma13102216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Peening Methods on the Fatigue Properties of Titanium Alloy Ti6Al4V Manufactured by Direct Metal Laser Sintering and Electron Beam Melting

Abstract: Titanium alloy Ti6Al4V manufactured by additive manufacturing (AM) is an attractive material, but the fatigue strength of AM Ti6Al4V is remarkably weak. Thus, post-processing is very important. Shot peening can improve the fatigue strength of metallic materials, and novel peening methods, such as cavitation peening and laser peening, have been developed. In the present paper, to demonstrate an improvement of the fatigue strength of AM Ti6Al4V, Ti6Al4V manufactured by direct metal laser sintering (DMLS) and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…The same is true with the shot peening on an as-printed aluminum alloy AlSi10Mg [40]. These functionally flexible methods [36][37][38][39][40] were almost as effective as rolling.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The same is true with the shot peening on an as-printed aluminum alloy AlSi10Mg [40]. These functionally flexible methods [36][37][38][39][40] were almost as effective as rolling.…”
Section: Introductionmentioning
confidence: 65%
“…Hammer peening is applied to modify the subsurface structures by severe plastic deformation with subdivision and misorientation in the previously grown grains, and eliminate the growth textures and large columnar grains [36,37]. Surface modification processes such as cavitation peening, shot peening and laser peening methods were applied on Ti-6Al-4V samples fabricated with the use of direct metal laser sintering and electron beam melting [38], achieving 70-97% improvement in fatigue strength.…”
Section: Introductionmentioning
confidence: 99%
“…The alumina blasting treatment removed the metal particles, reducing Ra and Rz—that is, it was expected that the strength would increase as the stress concentration was reduced by smoothing the surface [ 21 ]. It was also thought that there could be a peeling effect due to the alumina blast treatment of the surface [ 19 , 28 ]. However, it was confirmed that oxygen and aluminum adhered to the sandblast-treated surface.…”
Section: Discussionmentioning
confidence: 99%
“…Because CAD/computer-aided manufacturing (CAD/CAM) technology has the advantage that the thickness and strength of the metal can be designed [ 12 , 16 ], it should be able to reproduce the mandibular morphology of individual patients and manufacture customized titanium mesh trays of sufficient strength [ 17 , 18 ]. However, such additive manufacturing also has a problem in that an incomplete dissolution layer is formed on the outer surface, which affects mechanical strength [ 19 ]. Regarding mechanical strength, SLM products are reported to outperform or be equivalent to EBM products [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…(A) Implant surface microstructure produced by electrophoretic deposition ( Surmeneva et al, 2019 ). (B) Microstructure of implant surface produced by laser peening ( Soyama and Takeo, 2020 ). (C) Surface microstructures of implants produced by hydrogel packaging ( Mieszkowska et al, 2020 ).…”
Section: Surface Modification Technologymentioning
confidence: 99%